Pemberitahuan Berita K-Pop serta Dampak terhadap Return Saham Perusahaan Industri Hiburan Korea Selatan - Hibia, Imroatus; Handayani, Revita Dwi (Universitas Darwan Ali, 2024)
This study aims to determine the influence of K-Pop news notifications on stock returns of South Korean entertainment industry companies. The research sample consisted of 6 entertainment companies with a research period of 2 years. There is a phenomenon of two big news regarding the hiatus of BTS and NCT which caused two different market reactions. The data used includes 1,320 good K-Pop news and 888 bad K-Pop news. Data collection was carried out through secondary data using dummy variables using a time estimate of 4 days, and data analysis using multiple linear regression with Eviews 9. The results of the research show that: 1). Good K-Pop news has a significant positive effect on stock returns of South Korean entertainment industry companies. 2). Bad K-Pop news has a significant negative effect on stock returns of South Korean entertainment industry companies. The implications of this study include: 1). Extending the research period to get a more comprehensive picture, 2). Using a different approach in investigating the impact of K-Pop news on stock returns of South Korean entertainment industry companies for a deeper understanding, which can provide useful information in making investment.